Investigating the Contributions of International Oil and Gas Firms to Local Development in Ghana: Dilemmas and Challenges - Nyukorong, Remy (European Scientific Journal, ESJ, 2020)
Ghana is relatively new to oil and gas extraction and there is little empirical knowledge about the key players in the oil and gas business, what they do to contribute to local socio-economic development, and the quandaries these firms struggle with while operating under difficult circumstances. The purpose of this study was to assess the contribution of international oil companies to local development in Ghana and to evaluate the challenges and dilemmas faced by these firms. The study adopted a qualitative, interpretive case study design that relied on face-to-face interviews and focus group discussions to gather primary data. Interview responses were analysed, compared, and categorised with the results of transcription of the focus group discussions, and later triangulated and interpreted to draw conclusions. The study revealed that most international oil companies in Ghana are transparent in reporting on their business activities and operations. Despite the efforts by these firms to support local development by funding developmental projects, paying taxes, and providing employment opportunities to local youth, international oil companies are still a target of criticism for unsatisfactory performance. Local populations would like to see extractive firms finance community infrastructural projects matching with local priority needs and focus more on impact rather than the quantity of money disbursed or the number of projects funded. International oil companies should change their engagement approach from a mere consultation to a realistic, democratic, and broad-based involvement of the publics. This study has enriched existing frameworks applied to evaluate business organisations’ contributions to local development.